2021
DOI: 10.1002/ueg2.12101
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of endoscopic submucosal dissection in a country with a low incidence of gastric cancer: Results from a prospective national registry

Abstract: Introduction: Endoscopic submucosal dissection (ESD) has become the treatment of choice for early gastric malignancies. In recent years, the ESD technique has been implemented in Western countries with increasing use. Objectives:To describe the results of gastric ESD in a Western country with a low incidence of gastric cancer. Patients and Methods:The prospective national registry was conducted over 4 years in 23 hospitals, including 30 endoscopists. Epithelial and subepithelial lesions (SEL) qualified to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The main characteristics of the 27 studies [ 8 - 11 , 18 - 40 ] are summarized in Table 1 . Nineteen (n=1344) were cohorts and 8 (n=531) case series.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 27 studies [ 8 - 11 , 18 - 40 ] are summarized in Table 1 . Nineteen (n=1344) were cohorts and 8 (n=531) case series.…”
Section: Resultsmentioning
confidence: 99%
“…While many countries with a high prevalence of H. pylori infection could greatly benefit from a screening program for GC, issues such as cost, medical insurance, and other social and economic problems must be overcome to implement a screening program on a national or global level. As for the implementation of ESD in countries with a low incidence of GC, while it has been reported that ESD could be safely and usefully performed in Western countries, the establishment of training methods is also an issue [ 58 ]. ESGE guidelines recommend performing at least 10 ESD procedures under expert supervision and 25 ESD procedures per year to maintain ESD performance [ 42 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Modifications to the standard ESD technique may allow for resection of the muscle layer as well. En bloc resection allows for complete histologic assessment and may provide a complete and curative resection [10 ▪▪ ,25 ▪▪ ,26 ▪ ]. There are an increasing number of western studies, which have looked at adaptation of this technique with promising results [27 ▪ –29 ▪ ].…”
Section: Management: Standard Endoscopic Therapeutic Modalitiesmentioning
confidence: 99%